Mission of the company, prosocial attitudes and job preferences: A discrete choice experiment - Jan Adrianus Non; Ingrid Rohde; Andries de Grip; Thomas Dohmen (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
We conduct a discrete choice experiment to investigate how the mission of high-tech companies affects job attractiveness and contributes to self-selection of science and engineering graduates who differ in prosocial attitudes. We characterize mission by whether or not the company combines its profit motive with a mission on innovation or corporate social responsibility (CSR). Furthermore, we vary job design (e.g. autonomy) and contractible job attributes (e.g. job security). We find that companies with a mission on innovation or CSR are considered more attractive. Women and individuals who are more altruistic and less competitive feel particularly attracted to such companies.
Keywords: J81; J82; M52; 330; Mission of the company; sorting; discrete choice experiment; job characteristics; social preferences